2011
DOI: 10.3892/etm.2011.342
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of postoperative exacerbation of interstitial pneumonia in patients with lung cancer and interstitial lung disease

Abstract: Abstract. Postoperative exacerbation of interstitial pneumonia in patients with lung cancer and interstitial lung disease has emerged as a serious problem. Therefore, the risk factors for postoperative exacerbation of interstitial pneumonia in patients with interstitial lung disease must be identified. We analyzed 22 patients diagnosed as having lung cancer with interstitial lung disease who underwent surgical treatment at the Kitasato University Hospital. Among the patients with lung cancer and interstitial l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Online supplemental table 2 illustrates the major studies 20 21 35 23 24 25 26 which have explored the impact of underlying UIP for patients who undergo major lung resection for NSCLC. Despite having a variable prevalence, some groups reporting up to 13%, 19 UIP is consistently recognised as a significant independent negative prognostic factor in terms of postoperative pulmonary complications, in-hospital mortality and overall survival ( online supplemental table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Online supplemental table 2 illustrates the major studies 20 21 35 23 24 25 26 which have explored the impact of underlying UIP for patients who undergo major lung resection for NSCLC. Despite having a variable prevalence, some groups reporting up to 13%, 19 UIP is consistently recognised as a significant independent negative prognostic factor in terms of postoperative pulmonary complications, in-hospital mortality and overall survival ( online supplemental table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…For thoracic surgeons, postoperative AE is the most critical postoperative complication in ILD patients with lung cancer and is challenging to manage. Several studies have identified predictors of postoperative AE, including advanced lung cancer, lack of postoperative steroid use, postoperative episode of inflammation, male sex, KL-6 level, HRCT pattern, predicted vital capacity, history of AE, surgical procedure [ 2 , 9 ], general anesthesia [ 10 ], and perioperative blood transfusion [ 11 ]. However, the results of these retrospective studies need to be confirmed for reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…The prediction and prevention of postoperative AE is quite important. Several reports suggest that the following items could be predictors of postoperative AE; patient age, the duration of postoperative drainage and intraoperative fluid balance [ 16 18 ], typical honeycombing and possible honeycombing patterns on the chest CT findings [ 19 ], and the I/M ratio, which is the ratio of the peak standardized uptake value (SUV) of the interstitial lung disease area to the mean SUV of the mediastinum [ 20 ]. Although medications are used to prevent postoperative AE of ILD [ 5 , 21 ], no evidence for prophylaxis has yet been established.…”
Section: Discussionmentioning
confidence: 99%